Real time coordination of overcurrent relays by means of optimization algorithm. - Yen Shih, Meng (2013)
Protection is widely used in all different voltage levels of the electrical power system: generation, transmission, sub-transmission and distribution etc. An overcurrent relay is a protection that is widely implemented in the sub-transmission and distribution systems due to its competing cost. Depending on the operative conditions and fault locations in a mesh system, the load or fault currents can circle in or out of the overcurrent relay's protective zone. Hence directional overcurrent relays are used to discriminate whether the fault is located in or out of the protective zone. The propose of coordinating the overcurrent relays is to encounter settings that minimize the operation time for faults within the protective zone and at the same time offering pre-specified timed backup for relays that are in the adjacent zones. So the maximum fault current that the relay detects in its protective zone must be greater than the fault currents in the adjacent zones. The above condition is met in radial systems, one source mesh systems and two source mesh systems where the sources are located symmetrically at the end. But the above condition is not always met in the multi-source mesh systems due to the numerous operative configurations. Since the systems cannot operate in the absence of protection, other protection principles must be used, i.e. impedance relay. It is then said that for certain operative configurations of mesh system, overcurrent protection principle is out of range or in other words reaches the limit of its protection principle [1].